Comparative effectiveness on survival of zoledronic acid versus pamidronate in multiple myeloma. Issue 3 (March 2015) - Sanfilippo, K. M.; Gage, B.; Luo, S.; Weilbaecher, K.; Tomasson, M.; Vij, R.; Colditz, G.; Carson, K.
Abstract: Zoledronic acid and pamidronate are the two bisphosphonates approved in the United States to reduce multiple myeloma skeletal complications. Little prior evidence exists comparing survival outcomes between the two. We evaluated the incidence of skeletal-related events and overall survival in patients with myeloma treated with zoledronic acid versus pamidronate using a cohort of 1018 United States veterans. At a median follow-up of 26.9 months, patients receiving zoledronic acid had a 22% reduction in risk of death compared to pamidronate (hazard ratio 0.78; 95% confidence interval, 0.67–0.92). The benefit persisted after controlling for potential confounders. Adjusted Cox modeling with inverse probability weighting and propensity score matching supported these findings. Zoledronic acid was also associated with a 25% decrease in skeletal-related events. Zoledronic acid is associated with increased overall survival and decreased skeletal-related events compared to pamidronate in patients with multiple myeloma and should become the preferred bisphosphonate.